Health Promotion in Schools - A Key to Improving Young People’s Health - Hampel, Katarzyna; Ucieklak-Jeż, Paulina; Bem, Agnieszka; Hajduova, Zuzana (Journal of Finance and Financial Law, 2023)
The purpose of the article. The presented research aims to analyze the impact of health education on students’ attitudes towards taking care of their health, the health of other people and the ability to create a healthy environment. The paper assumes that health education is provided in schools by the applicable law. The work presents an up-to-date perspective on the complex problem of how young people perceive health. Methodology. To verify the significance of the differences in the respondents’ assessments, statistical methods (non-parametric tests) were used: the U-Mann-Whitney test and the Spearman rank correlation coefficient. The calculations were made using Statistica. The research sample included young people from upper secondary and general education schools. The author’s questionnaire was used. The study was anonymous. Respondents completed the questionnaire voluntarily. The research was conducted between March and September 2023. Results of the research. The conducted empirical analyses and the results of the surveys allowed us to achieve the goal assumed in the introduction and confirmed that health education in secondary schools influences the shaping of students’ attitudes towards taking care of their health and the health of the community in which they live. By implementing health education at school – according to the core curriculum – students’ awareness and motivation to undertake activities to improve and maintain good health is increased. Additionally, practical skills are developed to help them use the acquired knowledge in everyday life, and pro-health attitudes are formed. Health promotion is, therefore, the key to improving the health of school children, preparing them for a healthy lifestyle and making informed choices about their health and the community in which they live.